2022
DOI: 10.2486/indhealth.2021-0283
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts in the workplace, negative acts and health consequences: evidence from a clinical evaluation

Abstract: Interpersonal conflicts at workplace are increasing in relation to high competitiveness and pressures at work, mainly connected with labor market globalization. Their manifestation is multifaceted in relation to different working conditions and they not only hinder health, performance, and job satisfaction, but can also harm people's rights and dignity. The study analyses issues related to work conflicts and adverse health consequences in 1,493 workers who approached a hospital service for work-related stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Conflicts stemming from discrimination, harassment, or unequal treatment in the workplace (Castellini et al, 2023). It's essential for any organizations to address conflicts proactively through open communication, conflict resolution strategies, and creating a positive work environment.…”
Section: Discrimination and Harassment Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts stemming from discrimination, harassment, or unequal treatment in the workplace (Castellini et al, 2023). It's essential for any organizations to address conflicts proactively through open communication, conflict resolution strategies, and creating a positive work environment.…”
Section: Discrimination and Harassment Conflictsmentioning
confidence: 99%
“…Understanding and managing these conflicts are crucial for maintaining a healthy work environment and promoting positive social and labor relations. We found that key aspects of the place of conflicts and social tensions in the workplace within the context of social and labor relations include sources of conflicts (differences in goals and values, power imbalances, poor communication) (Hyatt & Gruenglas, 2023); productivity and well-being (reduces productivity, employee well-being) (Castellini et al, 2023); conflict resolution mechanisms (mediation, communication channels, conflict resolution training) (Brummans et al, 2022); legal and ethical considerations (Hyatt & Gruenglas, 2023); diversity and inclusuion (Randel, 2023); organizational culture (Ferine et al, 2021); and leadership role (Babalola et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…The instances of conflicts in the clinical settings severely compromise the care processes and well-being of patients, which drastically reduces their confidence in the healthcare system. A real-world study by Castellini provides the incidence rates of significant sources of conflicts in the occupational sector [21].…”
Section: Literature Review Root Causes Of Conflicts In the Healthcare...mentioning
confidence: 99%
“…Potential conflicts barricade the professional communication between the healthcare teams, thereby leading to the avoidance of important patient concerns and sensitive treatment requirements. Conflicts eventually challenge care continuity, hinder diagnostic assessment, induce the frequency of unnecessary evaluations, add to the iatrogenic complications and increase the incidence of safety events [21]. The healthcare professionals engaged in workplace disagreements tend to deviate from their responsibilities, while their misunderstandings impact their patient management decisions [23].…”
Section: The Need For Conflict Preventionmentioning
confidence: 99%
See 1 more Smart Citation